Ijtihad and a modernist perspective towards Islamic law and thought - Kayadibi, Saim (Mehir Vakfi, 2008)
All aspects of life are subject to constant transformation, and the present rulings, which are interpreted by jurists, are no exception. Islam is a way of life and consequently the Islamic Law has to be interpreted in such a way that accommodates changing circumstances and solves new problems. Thus, the principle of ijtihâd represents a worldwide phenomenon for future development in legislation. The principle of ijtihad has a vital role to play for justice and equity to prevail. In order to meet the future needs of society, Islamic law has to interact with the circumstances of the present era. It is impossible to deny the fact that the terms of law (aḥkām) vary with changes in times, and it is based on custom and tradition, which are the details of law. “It is an accepted fact that the terms of law (aḥkām) vary with the change in the times”. If this principle is clarified, it will shed light on the issue at hand. Thus, it is very essential to explain what the renewal of aḥkām means. This study is investigated in two parts. The first part deals with the general overview of the concept of modernist approach with special reference to an historical backdrop and its period of formation and developments. The second part of this study is devoted to special emphasizes on modernist perspectives from the modern era.